The Culture of Literacy Among Students of Islamic Education Program: A Case at a Private Islamic University - Awaludin, Azis (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This study aims to determine the causes and obstacles faced by students of the Islamic Religious Education Study Program in carrying out literacy activities. This study used a qualitative descriptive approach, which provides an appropriate description or explanation that occurs in the field, with data collection methods namely observation, documentation and interviews. So that at the end of the study, it is expected to know the Literacy Culture of Students of the Islamic Religious Education Study Program which is useful as input for institutions/foundations as well as input for competent educators/lecturers. Based on the results of the study, it shows that the reading literacy culture among students is still very low, this is influenced by various factors. The first is the lack of awareness of students in obtaining books or not having books. Second, they prefer to hang out with friends by talking about things that are less likely to lead to learning on campus. Third, they prefer to play games and social networking than reading. Fourth, they are tired and unfocused because they have a side job to earn money for living. These factors arise from within students are generally due to laziness, lack of self-motivation. Although there have been efforts made by lecturers by giving lectures and the library to encourage students to practice a reading literacy culture. However, students themselves choose not to practice reading literacy culture. What is more important is how to optimize students who have a passion for reading and writing, which have added value as a source of information that can assist in carrying out the Tri Dharma of Higher Education